Characteristics and mechanisms of nitrogen transformation during chicken manure gasification in supercritical water. (November 2022) - Liu, Shi; Cao, Wen; Wang, Yu; Wei, Wenwen; Li, Linhu; Jin, Hui; Guo, Liejin
Graphical abstract: Highlights: Nitrogen was mainly distributed in the liquid and solid products after SCWG. Up to 98.82% of the total nitrogen was in liquid products at 750 °C. Nitrogen in liquid products was mainly in the form of anilines, indoles, and NH3 -N. The migration and transformation pathways of nitrogenous components were proposed. Abstract: Supercritical water gasification (SCWG) is a clean and efficient method for the energy utilization of biomass waste. Studying the behavior of nitrogen in feedstock during the SCWG process is essential because of its significant potential impact on the environment. In this study, the characteristics and mechanisms of nitrogen transformation during chicken manure gasification in supercritical water were investigated in autoclave reactors. The results revealed that temperature plays an important role in raw material conversion and product distribution, especially for nitrogenous components. In particular, the carbon gasification efficiency was 92.66 % at 700 °C, 10 wt%, and K2 CO3 as catalysts, implying that the chicken manure was nearly completely converted. NO x was not identified in the gaseous products. As the temperature increased, nitrogen in the raw material was mainly transferred to the liquid. This process is accompanied by the conversion of organic nitrogen to inorganic nitrogen, which is mainly present as NH3 -N in liquids. Finally, the migration pathways of nitrogenous intermediates were investigated. The hydrolysis of proteins and amino acids in the initial phases creates conditions for the Maillard reaction, forming nitrogenous heterocyclic compounds (NHCs). Most NHCs gradually ring-opened and eventually converted to CO2, H2, NH3, and other gases. Only a small number of NHCs undergo a series of polymerization reactions at lower temperatures to form nitrogenous carbon precursors that are challenging to gasify. This study provides a theoretical foundation for the targeted removal of nitrogen components during the SCWG of high-nitrogenous biomass.